2017
DOI: 10.1089/ten.tea.2016.0523
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myoblast-Seeded Vascularized Tissue Scaffolds in the Treatment of a Large Volumetric Muscle Defect in the Rat Biceps Femoris Muscle

Abstract: High velocity impact injuries can often result in loss of large skeletal muscle mass, creating defects devoid of matrix, cells, and vasculature. Functional regeneration within these regions of large volumetric muscle loss (VML) continues to be a significant clinical challenge. Large cell-seeded, space-filling tissue-engineered constructs that may augment regeneration require adequate vascularization to maintain cell viability. However, the long-term effect of improved vascularization and the effect of addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…MVF have been shown to improve tissue vascularization and integration; however, this has been primarily demonstrated in subcutaneous implantation, 20 skin flaps, 39 and dermal substitutes, 22,23 all of which are considerably thinner and thus closer to native vascular sources than the critical size bone defect used here. MVF have also been shown to increase tissue perfusion in VML models when delivered in collagen gel, 21,40 which allows for sprouting angiogenesis. 17,21,41,42 In this study, while in vitro viability of MVF was maintained in collagen sponge, the multicellular MVF first dissociated to single cells and then reformed networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MVF have been shown to improve tissue vascularization and integration; however, this has been primarily demonstrated in subcutaneous implantation, 20 skin flaps, 39 and dermal substitutes, 22,23 all of which are considerably thinner and thus closer to native vascular sources than the critical size bone defect used here. MVF have also been shown to increase tissue perfusion in VML models when delivered in collagen gel, 21,40 which allows for sprouting angiogenesis. 17,21,41,42 In this study, while in vitro viability of MVF was maintained in collagen sponge, the multicellular MVF first dissociated to single cells and then reformed networks.…”
Section: Discussionmentioning
confidence: 99%
“…MVF have also been shown to increase tissue perfusion in VML models when delivered in collagen gel, 21,40 which allows for sprouting angiogenesis. 17,21,41,42 In this study, while in vitro viability of MVF was maintained in collagen sponge, the multicellular MVF first dissociated to single cells and then reformed networks. This is not consistent with the sprouting angiogenesis typically observed within a collagen gel and may have contributed to the lack of effect of MVF on bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers developed pre-vascularized TEMGs and evaluated their ability to participate in skeletal muscle regeneration in vivo [246,247,[264][265][266][267]. Li et al created TEMGs with collagen hydrogels seeded with adipose-derived microvessels with or without myoblasts [264]. Upon implantation into a full thickness biceps femoris defect, vascularized constructs were unable to prevent fibrosis and did not support muscle regeneration; this may suggest the supportive role that vascularization plays in muscle regeneration.…”
Section: Angiogenesis and Innervationmentioning
confidence: 99%
“…This is clearly a necessary criterion for creating a tissue engineered construct for skeletal muscle, as it is a highly vascularized tissue. There have been several studies which have shown tissue engineered strategies which promote successful formation of vessels after VML injury (M.-T. Li et al, 2017;VanDusen, Syverud, Williams, Lee, & Larkin, 2014). Interestingly, in our critically sized VML defect with no treatment we saw increased vascular volume as compared to the contralateral control.…”
Section: Discussionmentioning
confidence: 99%